Revisiting the origin of cycling enhanced capacity of Fe3O4 based nanostructured electrode for lithium ion batteries. (November 2017) - Huang, Yuan; Xu, Zihan; Mai, Jiangquan; Lau, Tsz-Ki; Lu, Xinhui; Hsu, Yao-Jane; Chen, Yongsheng; Lee, Alex Chinghuan; Hou, Yanglong; Meng, Ying Shirley; Li, Quan
Abstract: We identify that reversible formation/decomposition of lithium oxide, pulverization of Fe3 O4 nanoparticles, and electrolyte reactions, are contributors to the enhanced capacity observed in the Fe3 O4 electrode upon long cycling. Introducing three-dimensional graphene foam to form a composite with Fe3 O4 nanoparticles largely increases the capacity (~ 1220 mA h g −1 vs. ~ 690 mA h g −1 ) and promotes the cycling induced capacity enhancement (an earlier capacity rise and a faster rising rate) of the Fe3 O4 electrode. Together with Fe3 O4 nanoparticles, the presence of graphene effectively promotes the electrolyte reactions and reversible formation/decomposition of lithium oxide. At the same time, activation of GF also occurs in the presence of Fe3 O4 nanoparticles, further increases the capacity of the nanocomposite. Graphical abstract: Highlights: Pulverization of Fe3 O4 contributes to enhanced capacity upon long cycling. The electrolyte reactions also contribute to enhanced capacity upon long cycling. Reversible formation/decomposition of lithium oxide serves as another contributor. Introducing graphene to Fe3 O4 results in enhanced capacity and cycling performance. Electrochemical activation of graphene occurs in the presence of Fe3 O4 .